Pengembangan Quizizz Sebagai Media Pembelajaran Bahasa Arab Kelas IV MI Darul Falah Salamkanci Tahun Ajaran 2022/2023 - Ngarofah, Siti; Nurhapsari Pradnya Paramita; Haerul Ahyar (Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
This research was motivated by the lack of innovation in media used by teachers in delivering Arabic language material, the use of school facilities such as laptops and projectors that have not been utilized optimally in learning, and the low value of Arabic language learning outcomes. . This study aims to (1) determine the process of developing Quizizz as a learning medium for Arabic for Class IV MI Darul Falah Salamkanci in the 2022/2023 academic year and (2) determine the quality of Quizizz as a learning medium for Arabic for Class IV MI Darul Falah Salamkanci in the 2022/2023 academic year based on assessments from media experts, material experts, and student responses. This research is development research, or research and development (R&D), using a 3D development model, namely, define, design, and develop. The subjects of this study include one media expert, one material expert, and twenty-six students of class IV MI Darul Falah Salamkanci. The object of this research is a learning application. The instruments used to assess the quality of the application include a questionnaire for assessing media experts, material experts, and student response questionnaires. The results of this study are (1) the development of Quizizz as a learning medium for Arabic for class IV MI Darul Falah Salamkanci, and (2) the quality of Quizizz as a learning medium for Arabic for class IV MI Darul Falah is included in the category of